New finding sites of Drosophila suzukii (Matsumura, 1931) in perennial crops of Zagreb County : Nova nalazišta vrste Drosophila suzukii (Matsumura, 1931) u višegodišnjim nasadima Zagrebačke županije - Pajač Živković, Ivana (Array, 2019)
The presence of invasive Drosophila suzukii (Matsumura, 1931) was investigated in three perennial crops (two orchards - Šurdovec and Donje Orešje and one vineyard - Donje Orešje) in the area of Zagreb county. Samples of D. suzukii were collected during the three-month period (from August 18th until November 18th, 2017) by using apple vinegar traps. The presence of D. suzukii was confirmed at all three investigated sites. In the orchard Šurdovec the lowest number (25 specimens) of D. suzukii was caught while the largest number (84 specimens) was caught in the orchard Donje Orešje. In all perennial crops D. suzukii was classified as eudominant species which implicates its invasive character. Sex ratio of D. suzukii at the orchard and vineyard Donje Orešje was female-biased while only in the orchard Šurdovec was male-biased which points to the further spread of the species in the area of Donje Orešje. The results of the research are a contribution to the knowledge of the distribution of this invasive species in the new areas of Zagreb County.